Members of the lichen photobiont genus Trebouxia show species-specific photo-physiological and transcriptome-level responses to high light - Poquita-Du, Rosa Celia (Journal of experimental botany, 2025)
© The Author(s) 2025. Published by Oxford University Press on behalf of the Society for Experimental Biology.